Roles of the immunoglobulin’s in food allergy - Wang, Junling; Qin, Bingyu; Liu, Shihao; He, Shaoheng (Medical Research Archives, 2025)
Food allergy refers to food allergen-induced and immunoglobulin (Ig)-mediated aberrant immune responses, and is a major cause of anaphylaxis across age groups. While IgE is the canonical effector that arms mast cells and basophils and triggers immediate hypersensitivity upon allergen re-encounter. Additionally, emerging evidence indicates that non-IgE subclasses, involving IgG, IgA, IgD and IgM, shape sensitization, clinical reactivity and the acquisition of tolerance in context-dependent ways, and even has diagnostic values on food allergy. In this review, we summarize current understanding of how each Ig subclass contributes to the pathogenesis, diagnosis and immunotherapeutic response evaluation of food allergy. We also highlight translational implications, including anti-IgE therapy, immunotherapy-driven subclass remodeling and the promise of multiplex immunoassays for personalized diagnosis and monitoring. Clarifying the coordinated and even contradictory functions of Ig subclass will refine risk stratification and accelerate precision immunotherapy for food allergy.